A case report on mixed pulmonary infection of Nocardia nova, Mycobacterium tuberculosis, and Aspergillus fumigatus based on metagenomic next-generation sequencing - Yan, Haiming; Li, Zhandong; Xia, Han; Li, Qixin; Bai, Honglian (Frontiers in Public Health, 2022)
Background: Pulmonary infection is one of the common complications of long-term use of glucocorticoids. Severe infections not only increase the length of hospital stay and treatment costs, but also cause progression or recurrence of the primary disease. Case description: Herein, we reported a case of mixed pulmonary infection secondary to glucocorticoid use. Rare pathogens such as Nocardia nova, Mycobacterium tuberculosis, Aspergillus fumigatus, cytomegalovirus were detected by metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid and lung puncture tissue. Combining the results of conventional pathogen detection and clinical symptoms, the patient was diagnosed with mixed pulmonary infection by multiple pathogens. After timely targeted medication, the patient was finally discharged with a good prognosis. Conclusion: To our knowledge, this case is the first case report of mixed pulmonary infection with pathogens including Nocardia nova, Mycobacterium tuberculosis, Aspergillus fumigatus, and human cytomegalovirus. As a new clinical diagnostic method, mNGS has great advantages in the diagnosis of diseases such as mixed infections.